Efficacy and safety of DBPR108 monotherapy in patients with type 2 diabetes: a 12-week, randomized, double-blind, placebo-controlled, phase II clinical trial. (2nd July 2020) - Wang, Wei; Yao, Jun; Guo, Xiaohui; Guo, Yushan; Yan, Chaoli; Liu, Kuanzhi; Zhang, Ying; Wang, Xiaoyue; Li, Hongmei; Wen, Zhongyuan; Wang, Xinling; Li, Shuangqing; et al.
Abstract: Objective: DBPR108, a novel dipeptidyl-peptidase-4 inhibitor, has shown great antihyperglycemic effect in animal models. This study was to evaluate the efficacy and safety of DBPR108 monotherapy in type 2 diabetes mellitus (T2DM). Methods: This was a 12-week, double-blind, placebo-controlled phase II clinical trial. The newly diagnosed or inadequately controlled untreated T2DM patients were randomized to receive 50, 100, 200 mg DBPR108 or placebo in a ratio of 1:1:1:1. The primary efficacy outcome was HbA1c change from baseline to week 12. Relevant secondary efficacy parameters and safety were assessed. The clinical trial registration is NCT04124484. Results: Overall, 271 of the 276 randomized patients, who received 50 mg ( n = 68), 100 mg ( n = 67), 200 mg ( n = 69) DBPR108 or placebo ( n = 67), were included in full analysis set. At week 12, HbA1c change from baseline was −0.04 ± 0.77 in placebo group, −0.51 ± 0.71, −0.75 ± 0.73, and −0.57 ± 0.78 (%, p < .001 vs. placebo) in 50, 100, and 200 mg DBPR108 groups, respectively. Since week 4, DBPR108 monotherapy resulted in significant improvements in secondary efficacy parameters. At end of 12-week treatment, the goal of HbA1c ≤7% was achieved in 29.85, 58.82, 55.22, and 47.83% of the patients in placebo, 50, 100, and 200 mg DBPR108 groups, respectively. The incidence of adverse events did not show significant difference between DBPR108 and placebo except mild hypoglycemia in DBPR108 200 mg group. Conclusions: The study results support DBPR108 100 mg once daily as the primary dosing regimen for T2DM patients in phase III development program.